A Frequency Agile Semicircular Slot Antenna For Cognitive Radio System. (28th April 2016) - Kumar, Rajeev; Vijay, Ritu
Abstract : A frequency agile antenna is proposed with its ground plane having a semicircular shaped slot which is capable of switching the frequency to different bands, one at a time, in the wide frequency range of 5.33 GHz to 9.90 GHz. To achieve frequency agility, switching of six RF PIN diodes which are placed along the slot length is done in various combinations. Frequency tuning ratio of about 1.85 : 1 can be achieved using this design. Results such as return losses, gain, bandwidth, and radiation patterns are presented in this paper.